A Review of eco-friendly Management of Alternaria Species - Jayapradha, C.; Raja, Yesu (Indian Journal of Hill Farming, 2017)
Alternaria diseases on crop plants cause huge yield losses and reduce the economic value of the crop plants in conventional production system and are very difficult to manage. Chemical fungicides like dithane M-45, antrocol, captan, difolaton, blitox-50 gave satisfactory control but are dangerous to the ecosystem. Other methods of managing Alternaria pathogens like use of bio- control agents, medicinal plants, various plant products etc. have some potential. This review is an effort to through some light on the different eco-friendly strategies for the management of Alternaria species under different agro- climatic conditions.